Nephrotic Syndrome Secondary to Podocytopathy in SARS-COV2 Infection (2023)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is characterized by pulmonary involvement. However, there are reports on patients also suffering from concomitant renal involvement, with clinical manifestations such as hematuria, proteinuria, elevated nitrogen levels and acute kidney injury. Objective: The present study reports two clinical cases of nephrotic syndrome associated with coronavirus disease (COVID-19). Clinical case presentation: Histological imaging by electron microscopy showed, in one case, evidence of minimal changes and fusion of podocytes pedicels, and in the other one, podocytopathy with pedicels loss (70 %) and focal sclerosis of capillary loops. Discussion: Proteinuria in COVID-19 can be secondary to glomerular and acute tubular lesions, with a multifactorial origin: Hemodynamic factors, cytokine storms, secondary infections, druginduced nephrotoxicity and direct viral infection (proximal tubule cells and podocytes). The latter mechanisms could be explained by SARS-CoV2 renal tropism. Conclusion: The present report presents two cases of nephrotic syndrome secondary to podocytopathy in patients suffering from acute COVID-19 infection.